FDI and Wages: Evidence from Firm-Level and Linked Employer-Employee Data in Hungary, 1986-2008 - John S. Earle; Álmos Telegdy; Gábor Antal (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
We estimate the effects of foreign direct investment (FDI) acquisitions on firm-average and worker-specific wages using universal firm-level panel data and linked employer-employee data for Hungary. Our identification strategy exploits a 23 year-long panel with 4,926 foreign acquisitions to match on pre-acquisition data and to control for fixed effects for firms, detailed worker groups, and worker-firm matches. The estimates after these adjustments imply positive effects of about 12-27 percent on average wages. In an extension to 983 foreign acquisitions subsequently divested to domestic owners, we find that much of the acquisition effect is reversed by divestment. Estimating by worker type, we find positive effects for each of 64 gender-age-education-tenure groups, for all major occupations, and for all deciles of the wage distribution; the magnitudes are fairly uniform except for some skill-bias defined by education, occupation, and wage quantile. Even incumbents show wage gains, although not as large as post-acquisition hires. The evidence implies little role either for measurement problems (in hours worked, compensation, or misreporting) or for residual selection (associated with firm or worker turnover), but suggests a strong cross-firm association of FDI wage premia with similar differentials in productivity.
Keywords: F23; J31; 330; foreign acquisitions; FDI; earnings; wage differentials; productivity; difference-in differences matching; Hungary; Lohn; Auslandsinvestition; Ausländisch; Übernahme; Lohnstruktur; Produktivität; Schätzung; Ungarn